UNDERSTANDING THE STUDENTS' ENGLISH LEARNING ACHIEVEMENT AND HOME ENVIRONMENT SUPPORTS DURING SCHOOL CLOSURE TO RESPOND TO PANDEMIC AT PRIVATE MADRASAH TSANAWIYAH AT-TAKWA SAMBAS - Hairiyanto; Eka Sartika; Fini Widya Fransiska; Aslan (Adisam Publisher, 2024)
Understanding the perception of students' English education through the support of parents and the home environment when responding to class closures, the government's policy to save students but opening classes remotely is a critical and exciting study to carry out. For this reason, we have interviewed ten student resource persons to gain their experience and understanding of learning English and support from home. The results of these interviews and also supported by a review of several related literature, we can finally conclude that learning English which produces a reasonably good reference through a support approach from home during the pandemic response, has resulted in, among other things, the role and activity of parents supporting students during significant learning. In terms of motivational learning facilities, mental and physical support, and other support, which is the direct expression of students during distance learning. The publication and analysis of student interview data were carried out using a phenomenological approach involving data coding techniques and analysis according to in-depth evaluation and interpretation to obtain relevant and valid data to answer problems. The findings of this data will be helpful in the development of English language studies supported by parents and the home environment for similar studies in the future.